A neutral water-soluble mitochondria-targeting polymer. Issue 67 (5th August 2019) - Geng, Yu; Zhong, Yin; Zhou, Quan; Chen, Siqin; Piao, Ying; Yin, Wei; Lu, Hua; Shen, Youqing
Abstract : A neutral water-soluble N -oxide polymer can expeditiously enter a cell's mitochondria, and even reach the mitochondria after i.v. injection, making it an ideal delivery carrier. Abstract : We report the first neutral and water-soluble polymer capable of strong mitochondrial targeting in vitro and in vivo, zwitterionic poly[2-( N -oxide- N, N -diethylamino)ethyl methacrylate] (OPDEA). OPDEA is quickly internalized via macropinocytosis by various cancer cells and transferred into the mitochondria, which slightly lowers the mitochondrial membrane potential as determined by the JC-1 assay.